Assessment of Radiological Air Contamination for Selected Places at Al-Tuwaitha Nuclear Site during Winter and Spring (Baghdad Science Journal, 2018)
This study presents the results of atmospheric particulates sampling using high volume air sampler for selected places at Al Tuwaitha nuclear site. The collected samples were analyzed for gross alpha /beta radioactivity using Ludlum model 3030 and measurement particles activity in Al Tuwaitha nuclear site and the surrounding areas for the period from 28/12/2016 to 13/4/2017.The measurement of activity concentrations ranged from (0.42±0.03 to 4.18±0.13) Bq/m3 for alpha particles and from(0.93±0.06 to 9.21±0.26) Bq/m3for beta particles. The activity concentration of nuclides inversely proportional with air temperature and wind speed while humidity is directly proportional with it. Highest value of activity concentration has been found at(Near nuclear and radiation safety directorate/ In the center of planning department/T9)while the lowest value has been found at (the right side of Nuclear application and researches directorate / building 61/T42). The results of this study show that the region has natural nuclides which are the daughters of the two decay series, namely the thorium and the uranium series. In both cases, it is a radioactive Radon isotope which can escape from the soil and ascend into the air.